The influence of the Constitution of Cádiz of 1812 and the Constitution of Philadelphia of 1787 on the jurisdictional function of independent Mexico in the Constitution of 1824 - Delgado Quintero, Andrea; Freyssinier y Dávila, Cochisse (Revista Internacional & Comparada de Derechos Humanos, 2024)
The present document explores the evolution of the Judiciary in Mexico, starting with the Constitution of 1824, which laid the foundations for the judicial organization of the independent country. It emphasizes the importance of studying the history and legal context that led to the promulgation of this Constitution, highlighting the influence of earlier documents such as the Constitution of Cádiz and the Constitution of Philadelphia. Although the Constitution of 1824 established a framework for the independence of the Judiciary, this independence was partial, as the interpretation of laws remained the responsibility of Congress. The structure of the Judiciary is addressed, which included a Supreme Court, Circuit Courts, and District Courts, and the limitations of its powers and lack of resources for effective functioning are mentioned. The analysis highlights the tension between federalism and centralism, as well as the complexity of a Judiciary influenced by Spanish and American traditions. Finally, it concludes that the organization and functioning of the Judiciary were not fully consolidated until later years, reflecting a historical context of instability and power struggles among different factions.
Keywords: Mexican history; independent Mexico; judicial branch; comparative judicial analysis; Constitution of United States of America; Constitution of Cádiz; Constitution of Mexico of 1824; Constituent Congress; separation of powers; federalism; autonomy; independency